NFAT5 represses canonical Wnt signaling via inhibition of β-catenin acetylation and participates in regulating intestinal cell differentiation - Wang, Q (Nature Publishing Group, 2013)
The intestinal mucosa undergoes a continual process of proliferation, differentiation, and apoptosis, which is regulated by multiple signaling pathways. The Wnt/β-catenin pathway has a critical role in this process. Previously, we have shown that the calcineurin-dependent nuclear factor of activated T cell (NFAT) is involved in the regulation of intestinal cell differentiation, as noted by the alteration of brush-border enzyme intestinal alkaline phosphatase (IAP) activity. Here, we show that calcineurin-independent NFAT5 interacts with β-catenin to repress Wnt signaling. We found that overexpression of NFAT5 inhibits, whereas knockdown of NFAT5 increases, TOPflash reporter activity and the expression of Wnt/β-catenin target genes, suggesting that NFAT5 inhibits Wnt signaling. In addition, we demonstrated that NFAT5 directly interacts with the C-terminal transactivation domain (TAD) of β-catenin, inhibits CBP interaction with β-catenin, and inhibits CBP-mediated β-catenin acetylation. Moreover, NFAT5 is expressed in the mucosa of human intestine, with the most pronounced staining in the most differentiated region near the epithelial surface. Knockdown of NFAT5 attenuated sodium butyrate (NaBT)-mediated induction of IAP and sucrase activities; overexpression of NFAT5 induced IAP promoter activity. In summary, we provide evidence showing that NFAT5 is a regulator of Wnt signaling. Importantly, our results suggest that NFAT5 regulation of intestinal cell differentiation may be through inhibition of Wnt/β-catenin signaling.